2020
DOI: 10.1155/2020/2351547
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epoxide Hydrolase 2 Gene Arg287Gln with the Risk for Primary Hypertension in Chinese

Abstract: Background. Epoxide hydrolase 2 (EPHX2) gene coding for soluble epoxide hydrolase is a potential candidate in the pathogenesis of hypertension. Objectives. We aimed to assess the association of a missense mutation, R287Q, in EPHX2 gene with primary hypertension risk and examine its association with enzyme activity of soluble epoxide hydrolase. Methods. This study involved 782 patients with primary hypertension and 458 healthy controls. Genotyping was done using TaqMan technique. Activity of soluble epoxide hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Alzheimer's disease [11], hypertension [12] and familial hypercholesterolemia [13]. In contrast, most studies of EPHX2 in cancer have thus far been limited to speci c tumor types and there has been no report on the association studies between EPHX2 and pan-cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease [11], hypertension [12] and familial hypercholesterolemia [13]. In contrast, most studies of EPHX2 in cancer have thus far been limited to speci c tumor types and there has been no report on the association studies between EPHX2 and pan-cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variants of the epoxide hydrolase (EPHX2) gene were associated with the development of HTN and CVDs. 10,12 The presence of the EPHX2 rs41507953 variant within Caucasians was reported to be a risk factor in coronary heart disease. 13 In addition, it was reported that EPHX2 rs41507953 variant can increase the risk of HTN and ischaemic strokes in Sweden males.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variants of the epoxide hydrolase ( EPHX2 ) gene were associated with the development of HTN and CVDs 10,12 . The presence of the EPHX2 rs41507953 variant within Caucasians was reported to be a risk factor in coronary heart disease 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPHX2 encodes soluble epoxide hydrolase (sEH) [4], which is an important enzyme in the degradation of endogenous lipid epoxide, especially the inactivation of epoxyeicosatrienoic acids (EETs) [5]. Dysregulation of EPHX2 contributes to the pathogenesis of several diseases, such as prostate, liver and kidney cancers[6-8], atherosclerosis [9], Parkinson's disease [10], Alzheimer's disease [11], hypertension [12] and familial hypercholesterolemia [13]. In contrast, most studies of EPHX2 in cancer have thus far been limited to speci c tumor types and there has been no report on the association studies between EPHX2 and pan-cancer.…”
Section: Introductionmentioning
confidence: 99%